Face processing in Williams syndrome is already atypical in infancy - D’Souza, Dean (Front Psychol, 2015)
Face processing is a crucial socio-cognitive ability. Is it acquired progressively or does it constitute an innately-specified, face-processing module? The latter would be supported if some individuals with seriously impaired intelligence nonetheless showed intact face-processing abilities. Some theorists claim that Williams syndrome (WS) provides such evidence since, despite IQs in the 50s, adolescents/adults with WS score in the normal range on standardized face-processing tests. Others argue that atypical neural and cognitive processes underlie WS face-processing proficiencies. But what about infants with WS? Do they start with typical face-processing abilities, with atypicality developing later, or are atypicalities already evident in infancy? We used an infant familiarization/novelty design and compared infants with WS to typically developing controls as well as to a group of infants with Down syndrome matched on both mental and chronological age. Participants were familiarized with a schematic face, after which they saw a novel face in which either the features (eye shape) were changed or just the configuration of the original features. Configural changes were processed successfully by controls, but not by infants with WS who were only sensitive to featural changes and who showed syndrome-specific profiles different from infants with the other neurodevelopmental disorder. Our findings indicate that theorists can no longer use the case of WS to support claims that evolution has endowed the human brain with an independent face-processing module.